PENGARUH KINERJA KEUANGAN TERHADAP RETURN SAHAM PERUSAHAAN PERTAMBANGAN GO PUBLIC di BURSA EFEK INDONESIA - Fergyani Ocfrin; Usep Syaipudin; Rialdi Azhar; Reni Oktavia (Institut Agama Islam Negeri Ponorogo, 2022)
This study will discuss the effect of financial performance on stock returns of mining companies that go public on the Indonesian stock exchange. This study uses secondary data. The population in this study are mining companies listed on the Indonesia Stock Exchange, and the year of the study was from 2013 to 2015. In this study, 3 independent variables with 2 control variables and one dependent variable were used. The data analysis used is Descriptive Statistics, Classical Assumption Test, and Multiple Linear Regression. While the hypothesis testing used in this study using the Feasibility Test Model (F) and Hypothesis Testing (t).The results showed that Earning Per Share (EPS) and Price Book Value (PBV) had a positive effect on stock returns. While the Debt To Equity Ratio (DER) has a negative effect on stock returns in mining companies listed on the Indonesia Stock Exchange.